1998
DOI: 10.1016/s0735-1097(98)00014-x
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic Coronary Angiography

Abstract: This new technique can be easily implemented on conventional angiographic equipment at no additional cost. It provides complete, operator-independent exploitation of the angiographic information, resulting in enhanced diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Rotational angiography (RA) for cardiac applications was first described in 1998 and was developed to improve both diagnostic and therapeutic interventions in cardiac disease [1]. RA can be performed with an image intensifier or flat detector system.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational angiography (RA) for cardiac applications was first described in 1998 and was developed to improve both diagnostic and therapeutic interventions in cardiac disease [1]. RA can be performed with an image intensifier or flat detector system.…”
Section: Introductionmentioning
confidence: 99%
“…Early observational data have suggested that contrast and radiation exposure may be reduced with the use of a single anteroposterior (AP) rotation of the imaging camera while providing similar percent stenosis image information [12][13][14]. These findings have not been previously corroborated in any randomized study.…”
Section: Introductionmentioning
confidence: 99%
“…Tommasini et al [8], using a manually rotated C-arm method, identified lesions that appeared to be critical on rotational angiography but were categorized as noncritical or insignificant with conventional methods. Rotational X-ray coronary angiography has also been implemented in a preliminary form on a conventional image intensifier system [9].…”
Section: Introductionmentioning
confidence: 99%